2016
DOI: 10.1111/cch.12374
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic health records by child primary healthcare providers in Europe

Abstract: There is marked heterogeneity in the use and functionalities of EHRs used among child primary child healthcare providers in Europe. More importantly, lack of critical paediatric supportive functionalities like growth tracking and vaccination status has been documented in some countries. There is a need to explore the reasons for these findings, and to develop a cross European paediatric EHR standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The answers were collated and published (Rigby, Kühne, Greenfield, Majeed, & Blair, 2018), and the key finding is shown in Figure 14.1. They correlate well with the findings of a slight earlier study by Grossman et al (2016) for a smaller number of countries and using a different data gathering network.…”
Section: Use Of Ehrs For Children In Primary Caresupporting
confidence: 89%
“…The answers were collated and published (Rigby, Kühne, Greenfield, Majeed, & Blair, 2018), and the key finding is shown in Figure 14.1. They correlate well with the findings of a slight earlier study by Grossman et al (2016) for a smaller number of countries and using a different data gathering network.…”
Section: Use Of Ehrs For Children In Primary Caresupporting
confidence: 89%
“…In Canada, the National Physician Survey reported that 63.8% of primary care practitioners use EHRs, 25 but without specifying the features of these systems. A survey of primary care physicians and pediatricians in 10 European countries reported a huge variation in the reported rate, where it ranged from 7% to 97% 4 …”
Section: Discussionmentioning
confidence: 99%
“…It is claimed that it can enhance the quality of patient care, 1 improve the coordination of medical care, 2 reduce medical errors, 3 and increase compliance with guidelines. 4 Primary healthcare settings are a critical part of healthcare, 5 and efforts are increasing to maximize the adoption of EHRs in these settings, 6 since they are patients' first point of contact with the healthcare system and play a key role in disease prevention and treatment. 2 The use of EHRs in primary care settings has many advantages, including improved documentation, generating automatic reminders, computerizing order entry, enhancing scheduling, and providing clinical tools and calculators.…”
mentioning
confidence: 99%
“…Otro estudio, llevado a cabo en Europa por Z. Grossman y col., 6 reportó grados de adopción de la HCE muy variables por parte de los pediatras de atención primaria, dependiendo del país. El trabajo reveló países con altos porcentajes de adopción de la HCE de hasta el 97 % en contraposición con otros que registraban solo el 7 %.…”
Section: Discusión Utilización De La Historia Clínica Electrónica En unclassified